This island our home [videorecording] the four seasons of taiwan. (Government Information Office, 2000)
Taiwan is blessed witha subtropical environment. With the exception of the aborigines, the majority of the people on Taiwan came from the Chinese mainland over the past 200 years. These groups work together for their common prosperity. The beautiful scenery, bright city lights, rich cultural heritage all contribute to Taiwan's appealing presence. Its cultural richness is a manifestation of strength and forthrightness. A true focus on the island reveals its abundant vitality and stunning scenery. It tells of the humanity and natural beauty of this island. These are the basis of the relationship between heaven and earth and between human beings.